Efficacy Of Pgf2α, Gnrh And Ovsynch Protocol In Postpartum Anoestrus Crossbred Cows - Mahour, S. S.; Nema, S. P.; Shukla, S.P.; Mehta , H. K.; Gupta, V.K. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
A study was conducted on 40 postpartum anoestrus crossbred cows to evaluate therapeutic efficacy of PGF2α, GnRH and Ovsynch protocol. The order of oestrus induction was 80, 60 and 20 per cent in treatment with PGF2α, GnRH and ovsynch protocol. PGF2α treated cows exhibited oestrus between 1- 4 days with a mean post treatment oestrus induction interval of 2.37 ± 1.33 days, GnRH treated group exhibited oestrus between 7-17 days with a mean post treatment oestrus induction interval of 10.16 ± 0.33 days, whereas cows in ovsynch treated group had fixed time artificial insemination without heat detection. It was observed that 50 per cent cows conceived in PGF2α and GnRH treated group while only 40 per cent cows were conceived in ovsynch treated group.